Biomimetic shark skin: design, fabrication and hydrodynamic function - Wen, L.; Weaver, J. C.; Lauder, G. V. (The Journal of Experimental Biology, 2014)
Although the functional properties of shark skin have been of considerable interest to both biologists and engineers because of the complex hydrodynamic effects of surface roughness, no study to date has successfully fabricated a flexible biomimetic shark skin that allows detailed study of hydrodynamic function. We present the first study of the design, fabrication and hydrodynamic testing of a synthetic, flexible, shark skin membrane. A three-dimensional (3D) model of shark skin denticles was constructed using micro-CT imaging of the skin of the shortfin mako (Isurus oxyrinchus). Using 3D printing, thousands of rigid synthetic shark denticles were placed on flexible membranes in a controlled, linear-arrayed pattern. This flexible 3D printed shark skin model was then tested in water using a robotic flapping device that allowed us to either hold the models in a stationary position or move them dynamically at their self-propelled swimming speed. Compared with a smooth control model without denticles, the 3D printed shark skin showed increased swimming speed with reduced energy consumption under certain motion programs. For example, at a heave frequency of 1.5 Hz and an amplitude of ±1 cm, swimming speed increased by 6.6% and the energy cost-of-transport was reduced by 5.9%. In addition, a leading-edge vortex with greater vorticity than the smooth control was generated by the 3D printed shark skin, which may explain the increased swimming speeds. The ability to fabricate synthetic biomimetic shark skin opens up a wide array of possible manipulations of surface roughness parameters, and the ability to examine the hydrodynamic consequences of diverse skin denticle shapes present in different shark species.